Iron nanoflorets on 3D-graphene-nickel: A âDandelionâ nanostructure for selective deoxynivalenol detection - Ong, C.C. (Elsevier Ltd, 2020)
Deoxynivalenol (DON), a cosmopolitan mycotoxin found in agricultural commodities causes serious health maladies to human and animals when accidently consumed even at a low quantity. It necessitates selective and sensitive devices to analyse DON as the conventional methods are complex and time-consuming. This study is focused on developing a selective biosensing system using iron nanoflorets graphene nickel (INFGN) as the transducer and a specific aptamer as the biorecognition element. 3D-graphene is incorporated using a low-pressure chemical vapour deposition followed by the decoration of iron nanoflorets using electrochemical deposition. INFGN enables a feasible bio-capturing due to its large surface area. The X-ray photoelectron spectroscopy analysis confirms the presence of the hydroxyl groups on the INFGN surface, which acts as the linker. Clear Fourier-transform infrared peak shifts affirm the changes with surface chemical modification and biomolecular assembly. The limit of detection attained is 2.11 pg mLâ1 and displays high stability whereby it retains 30.65 of activity after 48 h. The designed INFGN demonstrates remarkable discrimination of DON against similar mycotoxins (zearalenone and ochratoxin A). Overall, the high-performance biosensor shown here is an excellent, simple and cost-effective alternative for detecting DON in food and feed samples. Â© 2020 Elsevier B.V.